From the Editor - Lovrenčić, Alen (Journal of Information and Organizational Sciences, 2017)
Dear readers and authors, We are constantly striving to increase both quality and quantity of papers published in our Journal. Also, we are constantly endeavor to include the Journal in new scientific databases. In the meantime Journal of Information and Organizational Sciences is included in the Web of Science Core Collection - Emerging Sources Citation Index (ESCI) and we are hoping that we will become the full member of the Web of Science database in short time. In this issue of the Journal we are presenting nine high quality papers from authors from Europe, Africa and Asia, consisting of four survey papers, one preliminary communication and four original scientific papers. We hope that this issue will satisfy all your requests, and that you will find included papers interesting and scientifically challenging.